Material language for protest: collage in Allen Ginsberg's 'Wichita Vortex Sutra'. Issue 4 (2nd April 2020) - Cran, Rona
ABSTRACT: This essay offers a critical re-reading of Allen Ginsberg's 'Wichita Vortex Sutra' (1966), re-situating it within the wider context of twentieth-century collage. It argues that Ginsberg's use of collage enabled him to articulate and embody the anti-Vietnam protest movement during the counterculture of the 1960s. His recognition of the potency of 'images juxtaposed', discovered when writing 'Howl' (1956), enabled him to deploy a material language for protest, in which he adhesively combined the physical with psychic, the personal with the political, and the prophetic with the cathartic, but in which he also created a space where readers and poem might encounter each another affectively. Although much has been written about this poem, it has yet to be comprehensively read in the context of the collage tradition – a growing field of study within which it demonstrably sits. Reading it in this way – as an inheritor of and participant in a global political art-form predicated on resistance and fracture – positions the poem within a more extensive lineage than it has hitherto been assessed, and, most importantly, reveals the ways in which Ginsberg used collage both to demonstrate and to attempt to overcome what he saw as the complicity between language and the perpetuation of the war in Vietnam.